2020
DOI: 10.21203/rs.3.rs-37914/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Risk factors of Hypoglycaemia in Neonates at St. Paul’s Hospital Millennium Medical College Neonatal Intensive Care Unit, Ethiopia: A Cross Sectional Study

Abstract: Background Hypoglycaemia is a common metabolic abnormality seen in neonates that can cause preventable death. Its overall incidence has been estimated to be 1 to 5 per 1,000 live births, with higher incidence in at-risk populations. There is limited data regarding its prevalence and risk factors in developing countries like Ethiopia. Therefore, this study was aimed to determine the prevalence and risk factors of neonatal hypoglycaemia in neonatal intensive care unit (NICU) at Saint Paul’s Hospital Millennium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…This finding is consistent with another study conducted in Nigeria, which found that 28.3% 26 , and Ethiopia, 25% 8 . However, the finding is higher than the study conducted in Israel 22 , in Kenyatta National Hospital 14.7% 27 , in Tehran hospital 15.15% 28 , in India 21.2% 29 , and Uganda 2.2% 3 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with another study conducted in Nigeria, which found that 28.3% 26 , and Ethiopia, 25% 8 . However, the finding is higher than the study conducted in Israel 22 , in Kenyatta National Hospital 14.7% 27 , in Tehran hospital 15.15% 28 , in India 21.2% 29 , and Uganda 2.2% 3 .…”
Section: Discussionsupporting
confidence: 92%
“…Sampling procedure. The sample size was determined using the single population proportion formula by considering the following assumptions: 95% confidence interval, 5% margin of error (d), and taking the p value from the previous study conducted in St. Paul's Hospital Millennium Medical College Neonatal Intensive Care Unit, Ethiopia 8 . Therefore, the final sample size after adding 5% was 304.…”
mentioning
confidence: 99%
“…The unpublished finding indicated that neonatal hypoglycemia was 25% in St. Paul Millennium Hospital Medical College in Ethiopia. 2 The variation might be due to the fact the studies used transient hypoglycemia within 48 hours after delivery which in turn consists of physiological hypoglycemia that later remains the norm glycemic state after the physiological process (48 hour-72hours) duration. This discrepancy might arise due to the sample size variation and some clinical setup variation found among studies.…”
Section: Incidence Of Persistent Hypoglycemiamentioning
confidence: 99%
“…1 Most neonates have transient hypoglycemia which responds to treatment and is associated with a good prognosis compared with persistent hypoglycemia. 2 If hypoglycemia occurs after 48 hours of age is termed persistent pathological hypoglycemia by which clinical manifestations are generated in the short term with abrupt injury and neurodevelopmental sequelae in long-term effect. 3 4 In normal physiology, the neonates' random blood glucose level (RBS) drops by 25-30 mg/dL and may lower down to 55-60 mg/dL in the first three hours of life.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital has 20 neonatal beds. 13 Yekatit 12 Hospital Medical College is serving more than 5 million people in the catchment area. The hospital has 9 departments and 6 units and has 12 neonatal beds.…”
Section: Study Setting and Study Periodmentioning
confidence: 99%